2017
DOI: 10.1177/0890334416680180
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Breastfeeding in African American Mothers

Abstract: Women who participated in this study breastfed for longer durations than the national average for African Americans. Findings can inform practice and research efforts to improve breastfeeding rates in this population using lessons learned from successful women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 30 publications
4
46
0
Order By: Relevance
“…New digital media have already been used in a range of health contexts, including chronic disease, 28 winter preparedness, 29 general school health, 30 physical activity, 31 substance abuse, 32 mental illness, 32,33 dietary behaviour change 34,35 and breastfeeding. 36 Digital media have also been evaluated for efficacy in enabling health promoting capacity through processes such as information seeking 37 and holistic self-participatory care. 38 Further, these media also have been used in specific disease contexts, such as obesity 39 and breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…New digital media have already been used in a range of health contexts, including chronic disease, 28 winter preparedness, 29 general school health, 30 physical activity, 31 substance abuse, 32 mental illness, 32,33 dietary behaviour change 34,35 and breastfeeding. 36 Digital media have also been evaluated for efficacy in enabling health promoting capacity through processes such as information seeking 37 and holistic self-participatory care. 38 Further, these media also have been used in specific disease contexts, such as obesity 39 and breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Feelings of guilt for not finding BF easy [38], for taking time out of work to BF [66], or for continuing to BF although finding the practice aversive [71] were reported. Some mothers felt overwhelmed, anxious, and frustrated with the intensity and unpredictability of breastfeeding [37] and found that "breastfeeding was demanding, not as easy as it should seem, and required perseverance" [72]. Developing resilience to judgement, and recognizing that "everyone has something to say about breastfeeding" [35,66,73] are coping skills that mothers reportedly used to help maintain their BF goals.…”
Section: Distinct Attitudes Beliefs and Perceptions Of Mothers Thatmentioning
confidence: 99%
“…Mothers described individual (e.g., determination, self-efficacy for BF) and interpersonal (e.g., social support) coping resources as facilitators of BF maintenance [33,34,53,73]. Social support, "particularly enlisting a female relative, friend, or partner was important for BF continuation" [39,53,56,72,79,80], and one study [81] identified social media as a maternally perceived facilitator of BF duration and maternal support.…”
Section: Distinct Attitudes Beliefs and Perceptions Of Mothers Thatmentioning
confidence: 99%
See 2 more Smart Citations